Vitamin D Receptor (VDR) Gene Polymorphism in Kurdish Patients Diagnosed with Different Stages of Colorectal Cancer - Ahmad, Narmeen (Journal of Sulaimani Medical College, 2025)
Background Vitamin D, causally implicated in calcium metabolism and bone diseases, mediates its biological functions through binding to the vitamin D receptor (VDR). VDR acts as a transcription factor enhancing several gene expressions. Single nucleotide polymorphisms (SNPs) in the VDR gene have been associated with colorectal cancer (CRC) in different ethnic groups. Objectives The objective of this study was to investigate the association of four common SNPs in the VDR gene (FokI, BsmI, ApaI, and TaqI) with the risk of CRC in a Kurdish population. Methods In this study 100 CRC patients and 50 healthy individuals with age and gender matched were recruited. Genomic DNA samples were extracted from the peripheral blood cells and VDR gene SNPs (FokI, BsmI, ApaI, and TaqI) were identified using amplification refractory mutation system-polymerase chain reaction (ARMS-PCR). Results None of the four common SNPs in the VDR gene individually had any significant effect on CRC risk. The evaluation of haplotypes for FokI, ApaI, and TaqI SNPs revealed that FAT (OR= 3.322, 95% CI (1.747-6.317), p<0.05) might enhance CRC risk, while two of the haplotypes including faT haplotype (OR= 0.340, 95% CI (0.158 - 0.732), p< 0.05) and FaT haplotype (OR= 0.203, 95% CI (0.082 -0.505), p< 0.05) are protective against CRC development. Conclusion This study found that SNPs tested neither increase nor decrease the risk of CRC in the selected Kurdish population. This finding needs to be confirmed in a large sample size to understand the potential roles of the selected polymorphisms in CRC development.
Keywords: Colorectal cancer; Vitamin D; Vitamin D receptor; Kurdish; Single nucleotide polymorphisms; FokI; BsmI; ApaI; TaqI